Comparing students' study abroad experiences and outcomes across global contexts. (July 2021) - Davis, Kirsten A.; Knight, David B.
Abstract: In this study, we explored the influence of international destinations on student experiences and learning outcomes in study abroad by comparing outcomes across international tracks within a common global program. All students take the same semester-long course then travel on one of seven international tracks to different countries. Our study treated each international track as a case and used a mixed-methods approach to analyze students' journals kept while studying abroad to compare the experiences and learning outcomes of students across cases. This analysis revealed that although the cultural distance between the United States and the host culture appears to influence students' experiences, several other factors such as the presence of a foreign language and visible historical environment are also important to consider. These results provide insight for designers of global programs regarding the implications of choosing different international destinations as the focus of their programs.